Online Detection for Notoginseng Ingredients in Macroporous Resin Purification Process Using Near Infrared Technology in Combination with Partial Least Squares - ZHONG, R.X.; LONG, F.; LIN, D.S.; YANG, H.R.; WU, C.J. (Asian Journal of Chemistry, 2014)